Análise da aplicabilidade e vantagens dos sistemas de gestão da qualidade em laboratórios - Corrêa, Amanda Fortes (Universidade Federal de São Carlos, 2026)
The concept of quality has been present in human relations since the first connection between artisan and client. With globalization, there was a need to increase productivity to meet the demand and competitiveness of the market and its consumers, and, for this reason, production ended up being fragmented into different sectors or companies, making the exclusively artisanal work that concentrated all processes up to the final product in a single person unviable. At this point, controlling and guaranteeing the quality of services and products is a crucial issue to meet the internal requirements of the company and especially its clients, whose satisfaction is of paramount importance to guarantee the sustainability of the business. The objective of this work is to analyze and present the main points of the structure of a quality management system (QMS) focusing on its applicability in laboratories, comparing applicable standards in this sector, such as ABNT NBR ISO 9001, ABNT NBR ISO/IEC 17025 and GLP monitoring. Furthermore, this work presents the impacts generated by the implementation and certification of a QMS (Quality Management System) for industry and the market, and offers a perspective on how adopting a quality culture can positively influence chemistry education, introducing students to this concept that will accompany them throughout their professional careers. This work also discusses quality tools and how they can be used in the daily operations of companies for verification, measurement, analysis, and proposing solutions to problems or failures. It concludes that the application of a QMS is of great importance to the chemical industries in the Brazilian and global markets, leading the organization to a new level of credibility and competitive advantage by standardizing processes, reducing costs, and increasing customer satisfaction, thus ensuring the sustainability of the business.
Applicability and advantages of quality management systems in laboratories: an analysis
Keywords: SGQ; Sistema de Gestão da Qualidade; Gestão da Qualidade em Laboratórios; ISO 9001; ISO/IEC 17025; BPL; CIENCIAS EXATAS E DA TERRA::QUIMICA; 12. Consumo e Produção Responsáveis; 8. Trabalho Decente e Crescimento Econômico